The Caribbean in a changing world : surveying the past, mapping the future. - Smith, Livingston; Fullerton-Cooper, Stephanie; Gordon, Erica; Bodden, Alexandra (Cambridge Scholars Publishing, 2016)
This collection is a critical reflection of the evolution of Caribbean countries since the demise of the West Indies Federation in 1962. At this historical juncture, some territories opted for independence while others remained dependent territories. The volume examines Caribbean societies in comparative and general ways, covering aspects of their ongoing development and challenges. It covers such areas as Caribbean integration, the state of human capital and social policy in the region, the education sector, Caribbean economic sustainability, and, significantly, the physical environment of the Caribbean. A central question has always been: should these territories have gone independent or stayed under some British tutelage? The book addresses this question, illustrating that these island states have made considerable progress, especially in the maintenance and deepening of democratic practices. Vol. 2: 9781443809979.